A review of 20 years of takaful literature using a systematic method. Issue 1 (10th January 2022) - Ansari, Zahin
Abstract : Purpose: The study aims to summarize the 20 years of literature published in takaful between 2000 and 2019 and propose some key areas as the directions for future research. Design/methodology/approach: The present study utilizes the systematic method of reviewing the literature. The SCOPUS database has been accessed, and 96 articles have been accounted for the analysis. The articles are grouped in their exclusive themes, such as consumer behavior, financial and nonfinancial performance, takaful models, human resources and governance. Findings: Takaful research has widely covered marketing, finance, human resource, governance and stresses on its legal issues. Both qualitative and quantitative methodologies have been employed. The research gaps have been classified based on the respective areas. Large share of current body of takaful literature consists of the studies related to the application of behavioural theories to examine the behavioural intention to take up takaful services. Originality/value: The study enriches the literature of takaful by reviewing articles according to their respective themes, thereby contributing to the significant findings missing from existing literature surveys.